Formation pathways and precursors of furfural during Zhenjiang aromatic vinegar production. (30th August 2021) - Gong, Min; Zhou, Zhilei; Liu, Shuangping; Zhu, Shenghu; Li, Guoquan; Zhong, Fang; Mao, Jian
Highlights: The formation of furfural in Zhenjiang aromatic vinegar (ZAV) was investigated. Furfural mainly formed in decoction process while HMF formed in decoction and aging. Multicomponent simulated model of cereal vinegar was used to explore the precursors. Multiple pathways were confirmed for furfural formation in cereal vinegar. Ribose, xylose, arabinose, uronic acids, and pentosan were the main precursors. Abstract: As a flavor and quality parameter, furfural has potential undesirable effects. This study aimed to elucidate furfural formation, including generation, pathways, and possible precursors during the production of Zhenjiang aromatic vinegar. A cereal vinegar model, rich in saccharides, amino acids, and organic acids, was used to explore the potential precursors. Furfural and 5-hydroxymethylfurfural (HMF) mainly generated during the decoction process, but the HMF also increased during the aging process. Three pathways were found to coexist for the formation of furfural: (i) the Maillard reaction induced by saccharides and nitrogenous compounds, (ii) the direct cleavage of pentose, and (iii) indirect conversion from pentosan, which only made a minor contribution. Furfural was not formed from HMF or l -ascorbic acid in vinegar. Instead, ribose, xylose, arabinose, galacturonic acid, glucuronic acid, and pentosan were the main precursors. These insights may be useful for the risk/benefit balance and improve the flavor quality and safety.